The importance of the care plan for cancer patients in palliative care developed by nurses from the Family Health Strategy (Research, Society and Development, 2021)
Objective: The present study aimed to describe the importance of the care plan in nursing care for cancer patients who need palliative care performed by professionals in the Family Health Strategy. Methods: Study of integrative literature review, developed through systematic research in the PUBMED and VHL database. The bibliographic review was restricted to publications from the last five years. The analysis of the results was done critically, ending the process of inclusion and exclusion of works that do not fit the proposed theme, ensuring the validation of the review and selected works. Results: The results found emphasize that the nurse offers assistance that provides means that provide an effective coping with the disease, by reducing the impact of symptoms on cancer patients. Conclusion: The importance of the nurse in palliative care at home was evidenced, who works by offering assistance based on humanization, comfort and dignity during the individual's terminal life process.